A sulfide-sensor and a sulfane sulfur-sensor collectively regulate sulfur-oxidation for feather degradation by Bacillus licheniformis - Chao Tang; Jingjing Li; Yuemeng Shen; Menghui Liu; Honglei Liu; Huaiwei Liu; Luying Xun; Yongzhen Xia (Communications Biology, 2023)
The feather-degrading bacterium Bacillus licheniformis MW3 contains a sulfur-metabolizing gene cluster, in which one sulfide-sensor and one sulfane sulfur-sensor synergistically control gene expression, enabling the bacterium to grow on bird feathers.